Benchmarking the Current Employment Statistics national estimates. - Manning, Christopher D.; Stewart, John R. (Monthly Labor Review, 2017)
The Current Employment Statistics (CES) survey is a large monthly survey of approximately 147,000 businesses and government agencies that represent about 634,000 individual worksites. It is used to produce detailed industry estimates of employment, hours, and earnings for the nation, states, and metropolitan areas. The CES program benchmarks its all-employee series annually to reanchor samplebased employment estimates to full population counts. This process improves the accuracy of the CES allemployee series by replacing estimates with full population counts that are not subject to the sampling or modeling errors inherent in the CES monthly estimates. These population counts are derived from administrative records and are much less timely than the sample-based estimates. However, they provide a near census of establishment employment. The authors describe the procedures currently used to benchmark the national CES all-employee estimates.